FABRICATION AND RULA ANALYSIS OF HAND-ARM REHABILITATION TRAINER FOR CHILDREN SUFFERING FROM CEREBRAL PALSY (Jurnal Mekanikal, 2024)
Cerebral palsy (CP) is a condition that affects a person’s mobility, muscle tone, and posture, resulting in disability. Individuals with CP often require the assistance of a caregiver to carry out their daily activities. Hence, strengthening their hands through exercise is critical in increasing voluntary control. A hand-arm trainer is a tool that provides assistive training for CP patients during therapy to strengthen their hands. It improves motor skills, particularly in the forearm and wrist areas, because one of the most important functions of the limbs is the ability of the hands to grab and hold objects. This study was conducted to develop a hand-arm trainer for children with CP aged six to twelve years old who have Gross Motor Function Classification System (GMFCS) Level III and IV.  The outstanding design was selected based on the highest score. Using the Pugh Concept Selection Method, Design 2 was chosen because it received the highest-ranking score compared to the other two designs. According to SOLIDWORKS simulation results, the maximum stress for Design 2 is 19.845 x 107 N/m2, while the maximum yield stress is 22.059 x 107 N/m2. The selected raw materials for Design 2 cost approximately RM 49.30 and weigh 5.438 kg. Adjustable height, adjustable resistance, and ease of maintenance are just a few features of the chosen hand-arm trainer in fabricated Design 2. The level of risk of disorder using Rapid Upper Limb Assessment (RULA) was conducted in accordance with the anthropometric dimensions of children under 12 years old. The detailed design of manikin posture is modelled and analysed. A RULA score of 3 was obtained, indicating that the person is working in a posture that could present some risk of injury from their work posture. Therefore, a change in work posture may be necessary to avoid the risk of injury.
Keywords: Cerebral palsy, hand-arm trainer, Solidworks; RULA, rehabilitation